Case Report: Mechanical hemolysis resulting from left ventricular outflow tract obstruction after aortic valve replacement relieved by transapical beating-heart septal myectomy - Kang, Qingwen; Tian, Jie; Zhu, Ying; Zhou, Wei; Wei, Xiang; Liu, Yani (Frontiers in Cardiovascular Medicine, 2024)
Background: Aortic stenosis (AS) in combination with left ventricular outflow tract obstruction (LVOTO) has occasionally been reported. However, it is a challenge to make a precise diagnosis and to treat this combination successfully because of the hemodynamic interaction between the two conditions. Case summary: A 56-year-old male patient who had been diagnosed with severe AS and asymmetric left ventricular hypertrophy, underwent aortic valve replacement (AVR) and a conventional septal myectomy. Immediately after the procedure, significant systolic anterior motion and mitral regurgitation developed, necessitating a surgical mitral edge-to-edge repair. Ten days after the procedure, the patient developed hematuria and LVOTO, which was confirmed by echocardiography. Because the LVOTO might have been the cause of the hematuria, the patient underwent alcohol septal ablation, but this had little effect. Three months later, transapical beating-heart septal myectomy (TA-BSM) was performed in our hospital. Postoperatively, the LVOTO had been significantly ameliorated and the hematuria had resolved. Conclusion: For patients with AS and LVOTO owing to a hypertrophic interventricular septum, inadequate amelioration of the LVOTO after AVR may lead to severe hemolytic hematuria. TA-BSM is a minimally invasive, safe, and effective surgical procedure for the amelioration of LVOTO in patients with aortic valve prostheses.